Beyond risk and safety? Identifying shifts in sex education advice targeted at young women. (May 2019) - Carr, Georgia; Bednarek, Monika
This study investigates changes in sex education advice from the 1990s to the 2010s. Our research is based on the analysis of an 88, 000 word corpus of advice columns from Dolly, a beauty, lifestyle and celebrity magazine aimed at Australian girls. The data are taken from 1994, 1995, 2014 and 2015, with both decades compared against each other to identify any potential shifts in sex education advice. The study combines corpus linguistic techniques with analysis of evaluative language (appraisal). Our analysis reveals a preoccupation with sexual health in the 1990s, shifting to a preoccupation with mental health in the 2010s. We identify a discourse of risk and safety and a discourse of pleasure in the 1990s, and medicalising and normalising discourses of mental health in the 2010s. We also consider interactions between question and answer in the advice pages, to better understand how discourses are introduced and negotiated in such written dialogic texts.